PENDAMPINGAN KOMUNITAS POKDARWIS PILANG DALAM PENGELOLAAN ANIMAL WASTE MENJADI KOMPOS ORGANIK UNTUK MENDUKUNG SUSTAINABILITY URBAN FARMING - Aji, Teguh Sarwo; Farida, Alimatul; Nugroho, Matheus (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Animal waste management is an environmental challenge that can be turned into an economic opportunity through the right approach. This service program aims to assist the Pokdarwis Pilang community of Probolinggo City in managing animal waste into organic compost to support the sustainability of urban farming. The Asset-Based Community Development (ABCD) approach is used to empower the community by utilizing existing local assets, such as animal waste, community skills, and infrastructure support. The service process includes five stages: Discovery, Dream, Design, Define, and Destiny. The Discovery stage focused on identifying local assets, where animal waste was found to be a valuable asset that was previously not managed properly. Through the Dream stage, the community formulated a shared vision to create a sustainable waste treatment system. The Design stage implemented technical training and procurement of composting infrastructure. At the Define stage, the community began to manage the waste treatment independently, followed by an evaluation of the results and social impact at the Destiny stage. The results showed an increase in the technical skills of Pokdarwis members, the establishment of a compost production unit, and changes in community behavior in waste management. In addition, the formation of partnerships with local markets helped improve the economic welfare of the community. The ABCD approach has proven effective in creating sustainable social change through community empowerment. Recommendations from this program are to expand the application of the ABCD approach to other communities and strengthen collaboration with stakeholders to support the sustainability of waste management and urban farming.